ÉTICA Y ECONOMÍA: LA DIMENSIÓN HUMANA (h) - Silva Vegas, Gerardo (2005)
The question of what the human dimension is, contains a great complexity, however, the modernity tries to respond in a simple way from a logic of having, that is to say, the man is measured by the level of his revenues. The search of new ways to know human´s dimension, allows to rediscover him in Aristotle´s act conception and its updating in Amartya Sen´s human capacities theory, a different focus that offers a much deeper answer from a being´s logical point of view. Nevertheless, to measure the human capacity is extremely difficult because it is an intangible one. This research is looking for the Hegelian idea of the objectivity, of the subjectivity for work, a starting point to level the difficulty and complement it with the classification of Abraham Maslow´s needs.